The Effect of Using Picture Word Inductive Model on Students’ Ability of SMAN 4 Pekanbaru in Writing Descriptive Texts - Kensi Yutaro Zoebar, Ramadhani; Delfi, Syofia; Aruan, Rumiri (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
The present study seeks whether there is a significant effect of using Picture Word Inductive model on students’ ability of SMAN 4 Pekanbaru in writing descriptive texts or not. This research uses quantitative method, namely by applied Pre-Experimental Design. The research sampling technique is Purposive Sampling. Class X.11 was selected as the sample with the total of 36 students. The instrument used is writing test. The hypothesis was tested using Wilcoxon Test. The research results show that there is a significant effect of using Picture Word Inductive model on students’ ability of SMAN 4 Pekanbaru in writing descriptive texts. This is proven from the students' average pre-test score, namely 60.08 (Poor), which experienced a significant increase after using PWIM in students' post-test average score into 82.25 (Very Good). Furthermore, the hypothesis test results show Sig. value 0.000 < 0.05 leads to the acceptance of the alternative hypothesis (Ha). Thus, it can be concluded that there is a significant effect of using Picture Word Inductive model on students’ ability of SMAN 4 Pekanbaru in writing descriptive texts. In addition, students' overall post-test scores have reached the standard of learning achievement criteria in Merdeka Curriculum after applying Picture Word Inductive model.